A droplet microfluidic platform for efficient enzymatic chromatin digestion enables robust determination of nucleosome positioning. Issue 17 (26th July 2018) - Xu, Yi; Lee, Jeong-Heon; Li, Zhaoyu; Wang, Liguo; Ordog, Tamas; Bailey, Ryan C.
Abstract : A microfluidic device was designed to efficiently fragment chromatin for downstream epigenetic assays. Abstract : The first step in chromatin-based epigenetic assays involves the fragmentation of chromatin to facilitate precise genomic localization of the associated DNA. Here, we report the development of a droplet microfluidic device that can rapidly and efficiently digest chromatin into single nucleosomes starting from whole-cell input material offering simplified and automated processing compared to conventional manual preparation. We demonstrate the digestion of chromatin from 2500–125 000 Jurkat cells using micrococcal nuclease for enzymatic processing. We show that the yield of mononucleosomal DNA can be optimized by controlling enzyme concentration and incubation time, with resulting mononucleosome yields exceeding 80%. Bioinformatic analysis of sequenced mononucleosomal DNA (MNase-seq) indicated a high degree of reproducibility and concordance (97–99%) compared with conventionally processed preparations. Our results demonstrate the feasibility of robust and automated nucleosome preparation using a droplet microfluidic platform for nucleosome positioning and downstream epigenomic assays.